Effect of Temperature on Corrosion Behavior of 304 Stainless Steel in Liquid Sn. Issue 9 (September 2018) - Jiajun, Chen; Xiping, Song; Han, Wang; Jingru, Liu
Abstract: Sn is a kind of low melting point metal and can be used as a liquid coolant due to its higher thermal conductivity. Compared with the currently used sodium liquid coolant, Sn is more chemically stable and unfeasible to fire or explore when contacting with air or water. The chemical reactions between Sn and 304 stainless steel that is widely used as primary circuit pipeline materials in fast reactor were researched, and the effect of temperature on the corrosion behavior between 304 stainless steel and liquid Sn was discussed. The results show that pitting happens when the temperature is lower than 823 K, and dissolution happens when the temperature is higher than 823 K.